Stev Theloke at 70 m of His Winning 100 m Backstroke Race at the 1998 Goodwill Games in New York - Rushall, B. S. (1999)
Video pictures (16 frames) and the appropriate technical/ biomechanical explanations for Stev Theloke at 70 m of His Winning 100 m Backstroke Race at the 1998 Goodwill Games in New York (the time for Stev Theloke's swim on this occasion was 54.43, the #1 ranked swim in the world for the year - he defeated Lenny Krayzelberg in this race).